Analisis Pengelolaan Badan Usaha Milik Desa (BUMDes) Gerbang Lentera Sebagai Penggerak Desa Wisata Lerep - Ihsan, Ahmad Nur; Setiyono, Budi (Journal of Politic and Government Studies, 2018)
BUMDes is Lembaga Usaha Desa (Village Business Institutions) that managed by the community and Government of the Village for the effort to strengthen the village’s economy and it formed based on the needs and potential of the village. This study aims to determine the management process of BUMDes in Lerep Village, West Ungaran District, Semarang Regency. The research approach used was descriptive qualitative. The data collected by using data collection techniques through interviews with informants who are considered to have the potential to provide information about the management process of the BUMDes Gerbang Lentera as Penggerak Desa Wisata Lerep (The Driver of the Lerep Tourism Village), also through interviews and documentation of the management results of BUMDes.The results of the study indicate that even though it is still new, BUMDes Gerbang Lentera is one of the BUMDes whose management is already good in Semarang Regency, so that it becomes another village reference for visits and comparative studies. The management process of BUMDes is going well in accordance with the objectives of the establishment of BUMDes. This can be proved by the business units that running well. The good factors for managing the BUMDes Gerbang Lentera are the available resources, the community participation and empowerment, government support and the existence of cooperation with third parties. Yet, there are still obstacles to the development of BUMDes, namely that, it is still difficult to find employees because the salaries are less promising.The conclusions of the management of BUMDes Gerbang Lentera Desa Lerep have been very good, especially compared to other BUMDes in Semarang Regency. Itis just like most BUMDes in other villages in Semarang Regency, it is still difficult to find employees because BUMDes still have difficulties in providing salaries.Keywords: Village Business Institutions, Management, Obstacles